Sondheim! the Birthday Concert ; a celebration of one of Broadway's greatest legends - Sondheim, Stephen 1930-2021 (Ellen M. Krass Productions, 2010)
This concert is a collection of some of Stephen Sondheim's most popular songs in celebration of his birthday
Recorded at Lincoln Center for the Performing Arts, New York, NY.
Overture and Introduction (07:30) -- America from West Side Story (05:22) -- Something's Coming from West Side Story (03:05) -- We're Gonna Be All Right from Do U Hear a Waltz (04:26) -- Don't Laugh from Hot Spot (05:03) -- Joanna from Sweeney Todd (03:11) -- You're Gonna Love Tomorrow / Love Will See Us Through from Follies (04:55) -- Too Many Mornings from Follies (05:06) -- The Road You Didn't Take from Follies (03:37) -- It Takes Two from Into the Woods (03:30) -- Old Friends from Merrily We Roll Along (02:30) -- Finishing the Hat from Sunday in the Park With George (03:55) -- Move On from Sunday in the Park With George (04:48) -- Pretty Women from Sweeney Todd (04:37) -- A Little Priest from Sweeney Todd (07:26) -- Good by For Now the theme from Reds (03:59) -- So Many People from Saturday Night (03:18) -- Beautiful Girls from Follies (02:47) -- Here's to the Ladies Who Lunch from Company (04:37) -- Losing My Mind from Follies (04:23) -- The Glamorous Life from A Little Night Music (04:15) -- Could I Leave You from Follies (04:02) -- Not a Day Goes By from Merrily We Roll Along (04:20) -- I'm Still Here from Follies (06:14) -- Sunday from Sunday in the Park With George (04:29) -- Happy Birthday and Credits (04:17)
Keywords: Geschichte 1900-2000; Music / 20th century; Composers; Concerts; Musicals / Excerpts; Music; Musik